MAPK SIGNAL PATHWAY INVOLVED IN ANTI-INFLAMMATORY EFFECT OF CHAIHU-SHUGAN-SAN AND SHEN-LING-BAI-ZHU-SAN ON HEPATOCYTE IN NON-ALCOHOLIC STEATOHEPATITIS RATS - Yang, Qin He; Xu, YongJian; Feng, Gao Fei; Hu, Chao Feng; Zhang, Yu Pei; Cheng, Shao Bing; Wang, Yan Ping; Gong, Xiang Wen (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Traditional Chinese medicine (TCM) has a thousands-of-years long history of use. Chaihu-Shugan-San (CSS) and Shen-ling-bai-zhu-San (SLBZS) are famous traditional Chinese herbal medicine formulas, which has been used in China for the treatment of many chronic diseases. This study investigated the anti-inflammatory effects of CSS and SLBZS on signaling molecules involved in p38 mitogen-activated protein kinase (p38 MAPK) pathway on hepatocytes of non-alcoholic steatohepatitis (NASH) rats induced by high fat diet. SD male rats were randomly divided into 8 groups: negative control group, model control group, high(9.6 g/kg/day)/low(3.2 g/kg/day)-dose CSS group, high(30 g/kg/day)/low(10 g/kg/day)-dose SLBZS group, high(39.6 g/kg/day)/low(13.2g/kg/day)-dose integrated group. The rats of NASH model were induced by feeding a high-fat diet. After 16 weeks, Hepatocytes were isolated from 6 rats in each group by collagenase perfusion. The liver histopathological changes and serum inflammatory cytokines TNF-α, IL-6 were determined. The proteins of TLR4, phosphor-p38 MAPK and p38 MAPK involved in p38 MAPK signal pathway were assayed. The statistical data indicated the NASH model rats reproduced typical histopathological features of NASH in human. CSS and SLBZS ameliorated lipid metabolic disturbance, attenuated NASH progression, decreased the levels of TNF-α and IL-6 in serum, as well as inhibited TLR4 protein expression, p38 MAPK phosphorylation, and activation of p38 MAPK. In conclusion, CSS and SLBZS might work as a significant anti-inflammatory effect on hepatocyte of NASH by inhibiting the activation of TLR4, p-p38 MAPK and p38 MAPK involved in p38 MAPK signal pathway. To some extent, CSS and SLBZS may be a potentially alternative and complementary medicine to protect against liver injury, alleviate the inflammation reaction, moderate NASH progression.